Encryption Techniques as Security Tools: A Technical Review (International Journal of Advanced Research in Computer Science, 2017)
We all know that the security problems are occurring seriously on the internet and ratio of cyber threats are also increasing rapidly. So, protecting the confidential, sensitive and some private information from unauthorized disclosure have become need of every organization or any individual. In computerized information, it will be required the techniques for providing the security for information. Various methodologies and algorithms such as cryptographic techniques or security tools have been developed for security point of view and work for searching new techniques is continuing. In this paper, we have reviewed on those encryption techniques, which are used to protect the information during transferring from one place to another on shared network. Sometimes these encryption techniques can be helpful to encrypt the storage information for keeping it secure. Here, we have tried to cover all those encryption/decryption techniques, which provide reliable security for information.Keywords: Cryptographic encryption, Symmetric key, Cipher text, Public key encryption, Wireless security, Digital signature